Application of optical diffraction radiation to a non-invasive low-emittance high-brightness beam diagnostics; Quantum aspects of beam physics - Karataev P.; Hamatsu R.; Muto T.; Araki S.; Hayano H.; Urakawa J.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Hirose T. (2004, 2004)
A simple approach for the beam size mesurements with optical diffraction radiationfrom a slit target is presented. The estimations show that it is possible to measure thebeam size with a resolution of about ~1µm. We developed a new approach forcalculating diffraction radiation characteristics from a rectangular finite size target witha rectangular opening in it to be able to estimate the influence of the coherentdiffraction radiation recoil.